KEPEMIMPINAN ISLAMI (STUDI FENOMENOLOGI PADA KEPALA SEKOLAH SMA BATIK 1 SURAKARTA) - Barra Bahtiar Aziz; Ahyar Yuniawan (JURNAL STUDI MANAJEMEN ORGANISASI, 2019)
Islamic leadership of the current headmaster is a determinant of the success and progress of an educational institution in obtaining blessings and ridho of Allah swt. Allah swt has given the example of the best man as an example of good for all people as an example of the leader of the earth that is the Prophet Muhammad saw. The purpose of this research is to know the understanding and implementation of Islamic leadership by the principal of SMA Batik 1 Surakarta, by applying Islamic leadership to the educational institution ie school, and find out what should be the implementation of Islamic leadership at school. The method used is qualitative method with phenomenology study approach. The reason for choosing the method is so that this research can be done in depth to know the understanding and implementation of Islamic leadership of headmaster in SMA Batik 1 Surakarta. The results of this study indicate that the principal SMA SMA 1 Surakarta already understand and apply Islamic leadership.